7th Mediterranean Conference and Exhibition on Power Generation, Transmission, Distribution and Energy Conversion (MedPower 201 2010
DOI: 10.1049/cp.2010.0896
|View full text |Cite
|
Sign up to set email alerts
|

A note on parameters of photovoltaic cells in dependence on irradiance and temperature

Abstract: This paper provides an analysis of the irradiance influence on photovoltaic cell efficiency in dependence on the cell construction, using the standard equivalent circuit describing solar cell. The influence of the series resistance is discussed in details and results of simulations are completed with experimental result obtained by measuring both crystalline silicon and CIS cells in broad intervals of irradiance and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…With increasing R s , both maximum power I mp V mp and FF decrease and consequently, efficiency decreases. This may also result in a decrease of efficiency with increasing irradiance at higher irradiance level [12].…”
Section: Special Issue On International Seminar On Power Semiconductomentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing R s , both maximum power I mp V mp and FF decrease and consequently, efficiency decreases. This may also result in a decrease of efficiency with increasing irradiance at higher irradiance level [12].…”
Section: Special Issue On International Seminar On Power Semiconductomentioning
confidence: 99%
“…-Si cell efficiency dependence on temperature and irradiance[12] Stacks of cell structures from materials of different band gaps a Two-material multiple junction structure b Energy converted in carrier generation in the case of a two cell stacks (a-Si:H on c-Si)[8] …”
mentioning
confidence: 99%
“…With increasing R s (or decreasing R p ) both maximum power I mp V mp and fill factor FF decrease and consequently, efficiency decreases. The influence of series resistance R s on PV cell efficiency in dependence on irradiance [13] is schematically shown in Fig.8. Parameters of PV cells depend on temperature.…”
Section: Photovoltaic Cells and Module Physics And Constructionmentioning
confidence: 99%
“…Summarizing the results of performed experiments, the authors emphasized signicant inuence of temperature on the crucial operating parameters of solar cells. In addition, the research described in [7] showed that the eciency of PV cells substantially depends on the level of solar radiation and resistance of the substrate material of which the cell is constructed. Simultaneously, in [7,8], it was conrmed that along with the increase of the operating temperature of a PV cell, it is possible to observe a signicant decrease in the values of indicators determining the quality of the considered PV cell such as open-circuit voltage, maximum power, ll factor and eciency.…”
Section: Introductionmentioning
confidence: 99%